Evaluation of Knowledge and Willingness of the Students of Larestan University of Medical Sciences About the Obligatory AIDS Test Before Marriage - Fatemeh Rahmanian (Beyhagh)
Background and Aims: AIDS has been recognized as the deadliest disease of the twentieth century. It is currently untreatable and the way to deal with the disease is to prevent AIDS. The aim of this study was to determine the knowledge and willingness of the students of Larestan University of Medical Sciences about the obligatory AIDS test before marriage. Materials and Methods: This descriptive cross-sectional study was performed on 600 students of Larestan University of Medical Sciences using simple sampling method. A self-made questionnaire consisting of two sections, awareness about AIDS and obligatory AIDS test before marriage, and students' willingness to perform obligatory AIDStest were designed. Data were analyzed using SPSS software. Result: The results showed that in the willingness section, 37.21% of female students and 40% of male students male students did not tend to the obligatory AIDS test before marriage. In the awareness section, 91.86% of female students and 86.47% of male students did not have sufficient information about obligatory AIDS test. Conclusion: The results of the study showed that more efforts are needed to provide counseling and information to young people and their families about the benefits of premarital screening. Therefore, performing premarital screening and providing appropriate counseling about the marriage of high risk individuals are among the cost effective prevention.